KETANGGUHAN KOPERASI DAN UMKM DI TENGAH TEKANAN EKONOMI: ANALISIS SEM-PLS KABUPATEN BERAU - Hasnawati; Tamam Rosid (ITB AAS Indonesia Surakarta, 2026)
Cooperatives and Micro, Small and Medium Enterprises (MSMEs) in Berau Regency face multiple structural pressures: raw material inflation, limited access to capital, low digital literacy, and regional policies that are not fully in favor of small business actors. This research examines the causal relationship between the variables of competitiveness, access to capital, digital literacy, regional government policy support on the resilience of MSME businesses in Berau Regency, East Kalimantan. The Structural Equation Modeling–Partial Least Squares (SEM-PLS) method was applied to 187 MSME respondents registered with the Berau Regency Cooperative and MSME Service in the 2023–2024 period. Empirical data shows that access to capital (path coefficient β = 0.412; p < 0.01) and digital literacy (β = 0.338; p < 0.01) are the main determinants of business resilience, while local government policies provide a significant moderating effect. The novelty of this study lies in the integration of Berau local wisdom variables, the involvement of the Berusu and Bajau Dayak traditional communities in informal distribution networks as control variables which have so far been ignored by the national literature. The findings recommend reforming regional ultra-micro credit policies as well as accelerating local ecosystem-based MSME digital transformation programs. Keywords: Berau Regency MSMEs; cooperative; SEM-PLS; business resilience; digital literacy; regional policy